2016
DOI: 10.1134/s1063783416050115
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular structure of electroactive polymer thin films

Abstract: This paper presents the results of an experimental investigation of the supramolecular structure of polydiphenylenephthalide thin films that exhibit effects of resistive switching. The supramolecular structure of the polymer has been investigated using small-angle neutron scattering in conjunction with atomic force microscopy. It has been found that the internal structure of polymer films consists of structural elements in the form of spheroids. The sizes of the structural elements, which were obtained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It was observed that polymer film thickness is about 115 nm, and structure element size in the deformed region is about 90 nm (Fig. 1, a observed earlier, in terms of the order of value [13]. To observe the current specifics inside the polymer layer in the mode of the constant interaction force maintaining, the deformed sections of polymer film were artificially made not on full depth of polymer film, i.e.…”
Section: Results Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was observed that polymer film thickness is about 115 nm, and structure element size in the deformed region is about 90 nm (Fig. 1, a observed earlier, in terms of the order of value [13]. To observe the current specifics inside the polymer layer in the mode of the constant interaction force maintaining, the deformed sections of polymer film were artificially made not on full depth of polymer film, i.e.…”
Section: Results Discussionmentioning
confidence: 88%
“…In any case the conducting channels forming is surely caused by the structure and properties of the corresponding dielectric (polymeric in our case) matrix. Studies [12,13] show that in case of smooth and even external surface the polymer film of PDP is internally structured, while internal structure (supramolecular structure) of films is associated with macromolecules association in initial solution. Before that, using mathematical model methods, it was observed that the most energetically favorable configurations of PDP macromolecules are linear syndiotactic and spiral isotactic.…”
Section: Results Discussionmentioning
confidence: 99%
“…Polymers of this class are soluble in organic solvents and have exceptional film-forming properties [5,6]. According to these results, continuous homogeneous films can be obtained by centrifugation from a solution in cyclohexanone on a metal surface with a thickness of up to several nanometers.…”
Section: Introductionmentioning
confidence: 99%